Artemisia spp.: An Update on Its Chemical Composition, Pharmacological and Toxicological Profiles. (5th September 2022) - Sharifi-Rad, Javad; Herrera-Bravo, Jesús; Semwal, Prabhakar; Painuli, Sakshi; Badoni, Himani; Ezzat, Shahira M.; Farid, Mai M.; Merghany, Rana M.; Aborehab, Nora M.; Salem, Mohamed A.; Sen, Surjit; Acharya, Krishnendu; et al.
Abstract : Artemisia plants are traditional and ethnopharmacologically used to treat several diseases and in addition in food, spices, and beverages. The genus is widely distributed in all continents except the Antarctica, and traditional medicine has been used as antimalarial, antioxidant, anticancer, antinociceptive, anti-inflammatory, and antiviral agents. This review is aimed at systematizing scientific data on the geographical distribution, chemical composition, and pharmacological and toxicological profiles of the Artemisia genus. Data from the literature on Artemisia plants were taken using electronic databases such as PubMed/MEDLINE, Scopus, and Web of Science. Selected papers for this updated study included data about phytochemicals, preclinical pharmacological experimental studies with molecular mechanisms included, clinical studies, and toxicological and safety data. In addition, ancient texts and books were consulted. The essential oils and phytochemicals of the Artemisia genus have reported important biological activities, among them the artemisinin, a sesquiterpene lactone, with antimalarial activity. Artemisia absinthium L. is one of the most famous Artemisia spp. due to its use in the production of the absinthe drink which is restricted in most countries because of neurotoxicity. The analyzed studies confirmed that Artemisia plants have many traditional and pharmacological applications. However, scientific data are limited to clinical and toxicological research. Therefore, further research is needed on these aspects to understand the full therapeutic potential and molecular pharmacological mechanisms of this medicinal species.